(untitled) (Pregled: časopis za društvena pitanja / Periodical for social issues, 2023)
Awareness about the importance of marketing of higher education institutions has been steadily growing amongst decision makers on international level. That trend is particularly noticeable in case of adult education programs, which need continual promotion since it is a type of non-formal education. In Bosnia and Herzegovina private universities and private providers of non-formal education programs have been promoting adult education for some time now. At the same time public universities, mainly influenced by the marketing myopia phenomenon, use promotional activities only sporadically. Therefore, for the purpose of improving promotion of adult education programs in public universities, a qualitative exploratory study has been conducted. The aim was to investigate attitudes and opinions of adults about promotion activities for adult education programs. Data was collected through focus groups from representatives of four generations: Baby Boomers, Generation X, Y and Z. Research results show that different generations have different needs and expectations when it comes to adult education programs. A generally positive attitude towards adult education programs has emerged. Values have been identified which could be communicated through promotion activities. Based on research results several recommendations are given for improvement of adult education promotion. Research results presented in this article directly contribute to achieving UNESCO’s Education for Sustainable Development 2030 agenda (priorities 1, 2, 3 and 5), contributing further indirectly to achieving Sustainable Development Goals 4, 8 and 10.